PENERAPAN METODE DATA ENVELOPMENT ANALYSIS UNTUK MENGUKUR KINERJA PROGRAM STUDI DI UNIVERSITAS TEUKU UMAR - ZAINAL PUTRA (Universitas Teuku Umar, 2019)
Abstract: The purpose of this study was to determine the performance of all study programs in the scope of Teuku Umar University and to know what steps should be taken by the study program so that its performance can be improved. With this research the top leadership at Teuku Umar University can obtain objective information on the performance of each study program in a multi-dimensional manner. So that it can carry out further action plans to improve performance in the future. This study uses the Data Envelopment Analysis (DEA) approach, using input variables, namely permanent lecturers, students, education staff, shopping and facilities and infrastructure. While the output variables include Non-Tax State Revenues (PNBP), national journals, accredited national journals, international journals, reputable national journals, accreditation, research and community service. A total of 18 study programs were treated as Decision Making Units (DMU). DEA was developed to measure how efficiently a DMU uses available resources to produce output optimally. DMUs that get a score of 1.00 are called efficient, while those in DMU that score less than 1.00 are called inefficient. The results of the analysis show that in 2017 there were 13 study programs (72.22%) obtaining an efficiency score of 1.00, namely Agrotechnology, Development Economics, State Administration, Sociology, Communication Science, Law, Civil Engineering, Mechanical Engineering, Industrial Engineering , Public Health, Marine Sciences, Aquaculture and Aquatic Resources. The remaining 5 study programs (27.78%) obtained an efficiency score of less than 1.00, namely Agribusiness, Agricultural Product Technology, Management, Accounting and Fisheries Sciences. In 2018 the number that obtained an efficiency score of 1.00 increased to 16 study programs (88.89%), namely Agrotechnology, Agricultural Product Technology, Development Economics, Management, State Administration, Sociology, Communication Science, Law, Civil Engineering, Engineering Machinery, Industrial Engineering, Public Health, Fisheries, Marine Sciences, Aquaculture and Aquatic Resources. The remaining 2 study programs or 11.11% obtained an efficiency score of less than 1.00, namely Agribusiness and Accounting. Keywords: Performance Measurement, Study Program, DEA Abstrak: Tujuan penelitian ini adalah untuk mengetahui kinerja seluruh program studi yang ada di lingkup Universitas Teuku Umar dan mengetahui langkah apa yang harus dilakukan oleh program studi agar kinerjanya dapat meningkat. Dengan penelitian ini jajaran pimpinan puncak di Universitas Teuku Umar dapat memperoleh informasi yang objektif terhadap kinerja masing – masing program studi secara multi dimensi. Sehingga dapat melakukan rencana tindakan lanjutan untuk meningkatkan kinerja di masa yang akan datang. Penelitian ini menggunakan pendekatan Data Envelopment Analysis (DEA), dengan menggunakan variabel input, yakni dosen tetap, mahasiswa, tenaga kependidikan, belanja serta sarana dan prasarana. Sedangkan variabel output mencakup Pendapatan Negara Bukan Pajak (PNBP), jurnal nasional, jurnal nasional terakreditasi, jurnal internasional, jurnal nasional bereputasi, akreditasi, penelitian dan pengabdian kepada masyarakat. Sebanyak 18 program studi diperlakukan sebagai Decision Making Units (DMU). DEA dikembangkan untuk mengukur seberapa efisien suatu DMU menggunakan sumber daya yang tersedia untuk menghasilkan output secara optimal. DMU yang memperoleh skor 1,00 disebut efisien, sedangkan terhadap DMU yang memperoleh skor kurang dari 1,00 disebut tidak efisien. Hasil analisis menunjukkan bahwa tahun 2017 terdapat sebanyak 13 program studi (72,22%) memperoleh skor efisiensi 1,00, yakni Agroteknologi, Ekonomi Pembangunan, Ilmu Administrasi Negara, Sosiologi, Ilmu Komunikasi, Ilmu Hukum, Teknik Sipil, Teknik Mesin, Teknik Industri, Kesehatan Masyarakat, Ilmu Kelautan, Aquakultur dan Sumber Daya Aquatik. Sisanya sebanyak 5 program studi (27,78%) memperoleh skor efisensi kurang dari 1,00, yakni Agrobisnis, Teknologi Hasil Pertanian, Manajemen, Akuntansi dan Ilmu Perikanan. Tahun 2018 jumlah yang memperoleh skor efisiensi 1,00 meningkat menjadi 16 program studi (88,89%), yakni Agroteknologi, Teknologi Hasil Pertanian, Ekonomi Pembangunan, Manajemen, Ilmu Administrasi Negara, Sosiologi, Ilmu Komunikasi, Ilmu Hukum, Teknik Sipil, Teknik Mesin, Teknik Industri, Kesehatan Masyarakat, Ilmu Perikanan, Ilmu Kelautan, Aquakultur dan Sumber Daya Aquatik. Sisanya sebanyak 2 program studi atau 11,11% memperoleh skor efisiensi kurang dari 1,00, yakni Agrobisnis dan Akuntansi. Kata Kunci: Pengukuran Kinerja, Program Studi, DEA